Preparation method of aluminum zinc oxide transparent conductive oxide film

Through the method of deficient nano alumina modulation of doped zinc oxide, the problem of uneven conductivity and transparency in traditional doping technology is solved, the carrier mobility and conductivity of zinc oxide aluminum film is improved, and the material performance is achieved. Improvement, while avoiding environmental and human harm, has economic and environmental advantages.

CN119320241APending Publication Date: 2025-01-17GUIZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411437939.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Traditional alternative doping techniques have uneven doping problems when improving the conductivity of transparent conductive oxides, resulting in uneven conductivity and transparency. Increasing doping concentration may reduce transparency, and may cause lattice distortion, affecting material performance.

Method used

By using defective nano-alumina modulation method to doped zinc oxide, a homogeneous zinc oxide aluminum precursor sol was prepared, spin-coated by sol-gel method and annealed at high temperature to form a uniform zinc oxide aluminum film, avoiding high Negative effects of doping.

Benefits of technology

Improve the carrier mobility and conductivity of zinc oxide aluminum film, ensure the transparency and uniformity of the material, avoid harm to the environment and the human body, and reduce material costs, which has great scientific significance and economical significance. and environmental value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320241A_ABST
    Figure CN119320241A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a zinc aluminum oxide transparent conductive oxide film. Preparing defective nano aluminum oxide sol; preparing a zinc oxide precursor solution; preparing defect aluminum oxide modulated and doped zinc oxide sol to obtain homogeneous zinc oxide aluminum precursor sol; spin-coating by a sol-gel method; the six dried glass sheets are respectively spin-coated with five different zinc oxide aluminum precursor sols with the doping ratio of 2%-10% and an undoped zinc oxide precursor solution, the spin-coating speed is 2000 rpm, the time is 30 s, and annealing treatment is conducted for 10 min at the temperature of 250 DEG C; detecting the mobility; the problem that the overall performance is affected due to non-uniform conductivity and transparency caused by non-uniform doping in an existing alternative doping technology is solved; and the transparency may be reduced by increasing the doping concentration to improve the conductivity, and traditional doping causes lattice distortion, changes the lattice constant, influences the grain size and shape and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive oxide thin films, and in particular relates to a method for preparing a zinc oxide aluminum transparent conductive oxide thin film. Background Art

[0002] Transparent conductive oxides (TCOs) are materials with high transmittance and low resistivity in the visible light spectrum. They have both good transparency and excellent conductivity. TCOs are widely used in consumer electronics, solar cells, LEDs, wearable devices, etc.

[0003] While TCOs are developing rapidly, there are also many technical problems that need to be solved. Since the advent of TCOs, how to improve its photoelectric performance, especially light transmittance and conductivity, has become the key to academic research. Therefore, there is an urgent need for a technology that can improve the conductivity of TCOs and improve its optical properties.

[0004] Traditional substitution doping technology is the most commonly used method to improve the optoelectronic properties of TCOs. Through traditional substitution doping, the carrier concentration or carrier mobility can be increased, and the conductivity of transparent conductive oxides can be improved. Doping can adjust the band gap width of the material and affect the absorption, reflection and transmission characteristics of the material. This allows the doped transparent conductive oxide to have good transparency in the visible and near-infrared range.

[0005] However, traditional alternative doping technologies have many disadvantages, such as: due to the scattering of ionized impurities, the charge carrier mobility μ decreases with the increase of the charge carrier density n. If the carrier concentration is increased, the carrier mobility will decrease, which will eventually make it difficult to further improve the performance of TCOs. Traditional alternative doping technologies have the problem of uneven doping, which may lead to uneven conductivity and transparency, thus affecting the overall performance. In addition, increasing the doping concentration to improve conductivity may reduce transparency, especially at high doping levels, where doping elements may introduce additional light absorption or scattering centers, thereby affecting optical properties. In addition, traditional doping can cause lattice distortion, change lattice constants, affect grain size and shape, etc., which may affect the application prospects of transparent conductive oxide films. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method for preparing a transparent conductive oxide film of zinc oxide aluminum to solve the problem that the alternative doping technology has uneven doping, resulting in uneven conductivity and transparency, thus affecting the overall performance. Increasing the doping concentration to improve conductivity may reduce transparency, and traditional doping may cause lattice distortion, change the lattice constant, affect the grain size and shape, and other technical problems.

[0007] The technical solution of the present invention is:

[0008] A method for preparing a zinc oxide aluminum transparent conductive oxide film, the method comprising:

[0009] Step 1, preparing defective nano-alumina sol;

[0010] Step 2, preparing a zinc oxide precursor solution;

[0011] Step 3, preparing defective aluminum oxide to modulate doped zinc oxide sol to obtain a homogeneous zinc oxide aluminum precursor sol;

[0012] Step 4, sol-gel spin coating; five zinc oxide aluminum precursor sols with different doping ratios of 2%-10% and undoped zinc oxide precursor solution were spin-coated onto six dried glass sheets at a spin coating speed of 2000 rpm for 30 seconds, and annealed at 250° C. for 10 minutes;

[0013] Step 5: Mobility detection.

[0014] The method for preparing defective nano-alumina sol comprises: dispersing five portions of defective nano-alumina particles with a mass increasing from 0.102 g to 0.51 g in 10 ml of an alcohol solvent respectively to prepare a nano-alumina precursor sol with a concentration of 0.1 M to 0.5 M; stirring the nano-alumina precursor sol at a temperature of 80° C. for 6 hours, and then ultrasonically treating it for 2 hours to obtain a bright yellow nano-alumina sol.

[0015] The preparation method of defective nano-alumina particles comprises: adding 10g of nano-alumina particles into a mixed solution of 25ml of 15wt% phosphoric acid and 25ml of 20wt% citric acid, soaking for 5min to complete the etching process, then filtering, washing the etched nano-alumina particles with deionized water, and obtaining defective nano-alumina particles after drying; or preparing 20ml of saturated aluminum chloride aqueous solution, then continuously stirring the solution at a temperature of 80°C, without sealing the bottle mouth during the stirring process, until a white-yellow precipitate is generated, placing the precipitate in a centrifuge for centrifugation at a speed of 7000rpm for 3min, repeating three times, and then calcining the powder obtained by centrifugation at a high temperature of 700°C for 12h, thereby obtaining defective nano-alumina.

[0016] The alcohol solvent is ethylene glycol methyl ether, methanol or ethanol.

[0017] The method for preparing a zinc oxide precursor solution includes: adding 1.4 g of an organic or inorganic zinc salt to 10 ml of an alcohol solvent to prepare a zinc acetate-ethylene glycol methyl ether solution with a concentration of 0.5 M, stirring the zinc acetate-ethylene glycol methyl ether solution at 75° C., adding 300 ul of ethanolamine during the stirring process, observing that the zinc acetate solution becomes transparent and clear, placing the zinc acetate solution at room temperature and stirring overnight, and the bottle mouth is not sealed during the stirring process, to obtain a zinc oxide precursor solution.

[0018] The organic and inorganic zinc salt is zinc acetate, zinc nitrate or zinc chloride; the alcohol solvent is ethylene glycol methyl ether, methanol or ethanol.

[0019] The preparation method of homogeneous zinc oxide aluminum precursor sol is as follows: take 1 ml of defective alumina sol of different concentrations and add 9 ml of zinc oxide precursor solution, respectively marked as 2%-10% doping ratio of zinc oxide aluminum precursor sol, stir the zinc oxide aluminum precursor sol at 60°C for 12h to obtain homogeneous zinc oxide aluminum precursor sol.

[0020] The drying method of the glass sheet comprises: ultrasonically cleaning the ITO glass sheet with water, ethanol and isopropanol in sequence, each cleaning process lasting 10 minutes, and placing the cleaned ITO glass sheet in a drying oven for drying for later use.

[0021] The mobility detection method is as follows: the prepared zinc oxide aluminum films with different doping ratios are coated with conductive carbon paste using a scraper method, and annealed at 100°C for 15 minutes. The zinc oxide aluminum films with different doping ratios and undoped zinc oxide films are placed on a solar light simulation instrument to record the volt-ampere characteristic curves and calculate the conductivity and carrier mobility respectively.

[0022] The calculation formula of conductivity is:

[0023] σ=l / AR (1)

[0024] σ represents the conductivity of the film, l represents the film thickness, A represents the active area of ​​the film, R is calculated from the VI curve, and R is the resistance value of the film;

[0025] The calculation formula of carrier mobility is:

[0026] J=9ε0ε r μV 2 / 8L 3 (2)

[0027] J represents the current density, μ is the carrier mobility, ε0 ​​(8.85×10-12F / m) is the vacuum dielectric constant, ε r is the dielectric constant of the material itself, V is the open circuit voltage of the film, and L is the thickness of the zinc aluminum oxide film.

[0028] The beneficial effects of the present invention are:

[0029] The present invention adopts a method of defective Al2O3 defect modulation doping ZnO to prepare AZO transparent conductive oxide. AZO does not contain any harmful components to human body and environment. Compared with tin-doped indium oxide (ITO) and fluorine-doped tin oxide (FTO), it has more advantages in environmental friendliness and cost.

[0030] Defect modulation doping technology forms a two-dimensional electron gas at the interface of the low-doped region where the two materials are in contact, and forms an impurity scattering center on the side of the interface of the highly doped material, which spatially separates the doped impurities from the transport layer. Compared with traditional alternative doping technology, it can bypass the limitation of carrier mobility in highly doped semiconductors, while improving the carrier concentration and carrier mobility. At the same time, defect modulation doping technology ensures the uniform distribution of doping elements in the oxide film, avoiding the impact on the transparency of the film. In addition, Al2O3 has a wide band gap and is generally considered to be an insulator, while the surface of nano-scale Al2O3 has a lot of defects, which can form defect energy levels and are easy to control, making it an ideal modulation doping material.

[0031] The AZO film prepared by the present invention can be applied to various display devices to ensure display effect and touch sensitivity. In addition, AZO can also be used as an electrode material to effectively improve the photoelectric conversion efficiency of solar cells. It can be applied to sensors, electronic components or other flexible electronic devices.

[0032] The present invention improves the conductivity and carrier mobility of ZnO through Al2O3 doping. AZO avoids excessive use of scarce metals, is harmless to the environment and human body, and can reduce material costs. In summary, AZO film will be very likely to replace traditional ITO and FTO, and its research and development has great scientific significance and good economic and environmental value.

[0033] The AZO film structure of the present invention comprises two main parts: a ZnO film for transmitting light of different wavelengths to achieve high absorptivity and conductivity; and an Al2O3 doping part for completing defect modulation doping of zinc oxide and improving the carrier mobility of the zinc oxide aluminum film.

[0034] The existing alternative doping technology has solved the problem of uneven doping, which leads to uneven conductivity and transparency, thus affecting the overall performance. Increasing the doping concentration to improve conductivity may reduce transparency. Traditional doping can cause lattice distortion, change lattice constants, affect grain size and shape, and other technical problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of the preparation process of the present invention;

[0036] Figure 2 (a) is the volt-ampere characteristic curve of AZO film when the doping concentration is 2%-6%;

[0037] Figure 2 (b) is the volt-ampere characteristic curve of AZO film when the doping concentration is 6%-10%;

[0038] Figure 3 The relationship between voltage and current density of AZO (6%) and ZnO thin films. DETAILED DESCRIPTION

[0039] Technical principle of the present invention:

[0040] The defect modulation doping technology described in the present invention refers to using the energy band arrangement of two chemically and structurally different materials to control the interface characteristics, thereby inducing one of the materials to achieve a charge carrier density that was previously unattainable.

[0041] In a semiconductor material, the number of carriers (free electrons or holes) is determined by the energy difference between the minimum value of the conduction band and the maximum value of the valence band. After the defect modulation doping technology is adopted, due to the wider band gap of the doped material, the Fermi level beyond the doping limit of the original doped material can be obtained. This induces the transfer of charges in the area near the interface of the doped material. This means that the doped transparent conductive oxide film can obtain a higher carrier mobility.

[0042] The present invention uses defective Al2O3 to modulate and dope transparent conductive oxide thin film zinc oxide. Since defective nano-alumina materials have a wide band gap, the Fermi level pinning effect at the interface between defective Al2O3 and ZnO can cause the Fermi level of ZnO to shift, thereby inducing charge transfer at the ZnO interface. In addition, the introduced defective Al2O3 forms an electron accumulation layer, which can increase the conductivity of the doped ZnO.

[0043] Compared with traditional modulation doping, the Fermi level of defective Al2O3 material is located near the interface of the doped semiconductor material, so that ZnO can obtain a Fermi level beyond the original doping limit, thus avoiding the limitation of traditional substitution doping on carrier mobility.

[0044] During the doping process, if the proportion of dopants is too high, the crystal structure will change, causing serious lattice distortion or phase change, thus affecting the performance and characteristics of the material. Therefore, we doped Al2O3 in the ZnO precursor solution at a ratio of 2%-10% to prepare zinc oxide aluminum film.

[0045] A method for preparing a zinc oxide aluminum transparent conductive oxide film, specifically comprising:

[0046] Step 1, preparing defective nano-alumina sol to prepare for defect modulation doping;

[0047] First, the preparation of defective nano-alumina particles, the scheme has the following options: Preparation scheme 1: Add 10g of nano-alumina particles to a mixed solution of 25ml phosphoric acid (15wt%) and 25ml citric acid (20wt%). Soak for 5min to complete the etching process. Etching can change the properties of the alumina surface, and produce pores and defects on the surface (the defect rates of oxygen vacancies, aluminum fillings, etc. in defective nano-alumina are related to the etching time, the concentration of the etching solution, etc.). Then filter, wash the etched nano-alumina particles with deionized water, and obtain defective nano-alumina particles after drying. Preparation scheme 2: Prepare 20ml of saturated aluminum chloride aqueous solution. Then continue to stir the solution at a temperature of 80°C, and the bottle mouth is not sealed during the stirring process until a large amount of white-yellow precipitate is generated. Put the precipitate into a centrifuge for centrifugation at a speed of 7000rpm for 3min, and repeat three times. Then the powder obtained by centrifugation is placed at a high temperature of 700°C for calcination for 12h. A large number of defects will be introduced in the entire process of preparing alumina, thereby obtaining defective nano-alumina.

[0048] Five portions of the prepared defective nano-alumina particles, with the mass increasing from 0.102 g to 0.51 g, were dispersed in 10 ml of ethylene glycol methyl ether (including but not limited to ethylene glycol methyl ether, and can include alcohol solvents such as methanol and ethanol) to prepare nano-alumina precursor sols with concentrations ranging from 0.1 M to 0.5 M. The purpose of this is to prepare nano-Al2O3 sols that can be directly added to ZnO precursor sols in a ratio of 2%-10%.

[0049] The nano-alumina precursor sol was stirred at 80°C for 6 hours and then ultrasonically treated for 2 hours to obtain a bright yellow nano-alumina sol. Long-term high-temperature stirring and ultrasonic treatment are conducive to the dispersion of nano-Al2O3.

[0050] Step 2, preparing a zinc oxide precursor solution to prepare doped defective aluminum oxide;

[0051] 1.4 g of zinc acetate (including but not limited to zinc acetate, and may include organic and inorganic zinc salts such as zinc nitrate and zinc chloride) is added to 10 ml of ethylene glycol methyl ether (including but not limited to ethylene glycol methyl ether, and may include alcohol solvents such as methanol and ethanol) to prepare a zinc acetate-ethylene glycol methyl ether solution with a concentration of 0.5 M, so as to control the microstructure and pore structure of the material, thereby regulating the performance of the material.

[0052] The solution was stirred at 75°C, and 300ul of ethanolamine was added during the stirring process. It was observed that the zinc acetate solution became transparent and clear. High temperature helps the dissolution of zinc acetate. In addition, the alkalinity of ethanolamine can neutralize the acidic groups, reduce the polarity of zinc acetate, and promote the dissolution of zinc acetate in ethylene glycol methyl ether.

[0053] The solution was stirred overnight at room temperature, and the bottle mouth was not sealed during the stirring process, to obtain a zinc oxide precursor solution, so that the ZnO precursor sol was fully oxidized, which was beneficial to the preparation of the film.

[0054] Step 3, preparing defective aluminum oxide to modulate doped zinc oxide sol, and preparing for spin coating;

[0055] Take 1ml of defective alumina sol of different concentrations and add 9ml of zinc oxide precursor solution, and mark them as zinc oxide aluminum precursor sol with 2%-10% doping ratio. The mixing of the two sols is conducive to adjusting the microstructure and pore structure of nano-Al2O3 defect modulation doped ZnO material, so as to obtain a uniform zinc oxide aluminum film.

[0056] The zinc oxide aluminum precursor sol is stirred at a temperature of 60° C. for 12 hours, so that the nano-alumina and the zinc salt are fully mixed to obtain a homogeneous zinc oxide aluminum precursor sol.

[0057] Step 4: Sol-gel spin coating.

[0058] The ITO glass sheet was ultrasonically cleaned with water, ethanol and isopropanol in sequence, with each cleaning process lasting 10 minutes. The cleaned ITO glass sheet was placed in a drying oven for drying.

[0059] Six dried ITO glass sheets were selected, and five different doping ratios (2%-10%) of zinc oxide aluminum precursor sol and undoped zinc oxide precursor solution were spin-coated on the six glass sheets. The spin-coating speed was 2000 rpm and the time was 30 s. The sheets were annealed at 250°C for 10 min.

[0060] Step 5: Mobility test

[0061] The prepared zinc oxide aluminum films with different doping ratios were coated with conductive carbon paste using a doctor blade method and annealed at 100°C for 15 minutes.

[0062] The zinc oxide aluminum films with different doping ratios and the undoped zinc oxide films were placed on a solar light simulation instrument (1000W / CM 2 )Record its volt-ampere characteristic curve and calculate its conductivity and carrier mobility respectively.

[0063] AZO thin film characterization:

[0064] The conductivity is very important for evaluating the performance of the zinc-aluminum oxide film, so the present invention characterizes the volt-ampere characteristic curve of the film, such as Figure 2 ab. The calculation formula of conductivity is as follows:

[0065] σ=l / AR (1)

[0066] Among them, σ represents the conductivity of the film, l represents the thickness of the film, A represents the active area of ​​the film, R is calculated from the VI curve, and R is the resistance value of the film. After calculation, when the doping concentration ratio is 6%, the conductivity of the zinc oxide aluminum film is the highest, which is about 1.44×10 -2 s / cm, while the conductivity in the undoped state is about 7.02×10 -3 s / cm.

[0067] The JV curve relationship of doped and undoped zinc oxide is as follows Figure 3 In order to further evaluate the effect of defect modulation doping of aluminum oxide on the mobility of zinc oxide, the present invention uses the following formula to calculate the carrier mobility of aluminum zinc oxide and zinc oxide:

[0068] J=9ε0ε r μV 2 / 8L 3 (2)

[0069] Among them, J represents the current density, μ is the carrier mobility, ε0 ​​(8.85×10-12F / m) is the vacuum dielectric constant, ε r is the dielectric constant of the material itself, V is the open circuit voltage of the film, and L is the thickness of the zinc oxide aluminum film. Through calculation, when the doping concentration ratio is 6%, the carrier mobility of the zinc oxide aluminum film is the highest, which is 65.01cm 2 ·V -1 ·s -1 , while the mobility of undoped zinc oxide is about 33.38 cm 2 ·V -1 ·s -1 .

Claims

1. A method for preparing a zinc oxide aluminum transparent conductive oxide film, characterized in that: The method comprises: Step 1, preparing defective nano-alumina sol; Step 2, preparing a zinc oxide precursor solution; Step 3, preparing defective aluminum oxide to modulate doped zinc oxide sol to obtain a homogeneous zinc oxide aluminum precursor sol; Step 4, sol-gel spin coating; Five zinc oxide aluminum precursor sols with different doping ratios of 2% to 10% and an undoped zinc oxide precursor solution were spin-coated onto six dried glass sheets at a spin-coating speed of 2000 rpm for 30 seconds, and annealed at 250° C. for 10 minutes. Step 5: Mobility detection.

2. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 1, characterized in that: The method for preparing defective nano-alumina sol comprises: dispersing five portions of defective nano-alumina particles with a mass increasing from 0.102 g to 0.51 g in 10 ml of an alcohol solvent respectively to prepare a nano-alumina precursor sol with a concentration of 0.1 M to 0.5 M; stirring the nano-alumina precursor sol at a temperature of 80° C. for 6 hours, and then ultrasonically treating it for 2 hours to obtain a bright yellow nano-alumina sol.

3. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 2, characterized in that: The preparation method of defective nano-alumina particles comprises: adding 10g of nano-alumina particles into a mixed solution of 25ml of 15wt% phosphoric acid and 25ml of 20wt% citric acid, soaking for 5min to complete the etching process, then filtering, washing the etched nano-alumina particles with deionized water, and obtaining defective nano-alumina particles after drying; or preparing 20ml of saturated aluminum chloride aqueous solution, then continuously stirring the solution at a temperature of 80°C, without sealing the bottle mouth during the stirring process, until a white-yellow precipitate is generated, placing the precipitate in a centrifuge for centrifugation at a speed of 7000rpm for 3min, repeating three times, and then calcining the powder obtained by centrifugation at a high temperature of 700°C for 12h, thereby obtaining defective nano-alumina.

4. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 2, characterized in that: The alcohol solvent is ethylene glycol methyl ether, methanol or ethanol.

5. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 1, characterized in that: The method for preparing a zinc oxide precursor solution includes: adding 1.4 g of an organic or inorganic zinc salt to 10 ml of an alcohol solvent to prepare a zinc acetate-ethylene glycol methyl ether solution with a concentration of 0.5 M, stirring the zinc acetate-ethylene glycol methyl ether solution at 75° C., adding 300 ul of ethanolamine during the stirring process, observing that the zinc acetate solution becomes transparent and clear, placing the zinc acetate solution at room temperature and stirring overnight, and the bottle mouth is not sealed during the stirring process, to obtain a zinc oxide precursor solution.

6. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 5, characterized in that: The organic and inorganic zinc salt is zinc acetate, zinc nitrate or zinc chloride; the alcohol solvent is ethylene glycol methyl ether, methanol or ethanol.

7. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 1, characterized in that: The preparation method of homogeneous zinc oxide aluminum precursor sol is as follows: take 1 ml of defective alumina sol of different concentrations and add 9 ml of zinc oxide precursor solution, respectively marked as 2%-10% doping ratio of zinc oxide aluminum precursor sol, stir the zinc oxide aluminum precursor sol at 60°C for 12h to obtain homogeneous zinc oxide aluminum precursor sol.

8. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 1, characterized in that: The drying method of the glass sheet comprises: ultrasonically cleaning the ITO glass sheet with water, ethanol and isopropanol in sequence, each cleaning process lasting 10 minutes, and placing the cleaned ITO glass sheet in a drying oven for drying for later use.

9. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 1, characterized in that: The mobility detection method is as follows: the prepared zinc oxide aluminum films with different doping ratios are coated with conductive carbon paste using a scraper method, and annealed at 100°C for 15 minutes. The zinc oxide aluminum films with different doping ratios and undoped zinc oxide films are placed on a solar light simulation instrument to record the volt-ampere characteristic curves and calculate the conductivity and carrier mobility respectively.

10. The method for preparing a zinc oxide aluminum transparent conductive oxide film according to claim 9, characterized in that: The calculation formula of conductivity is: σ=l / AR (1)σ represents the conductivity of the film, l represents the film thickness, A represents the active area of ​​the film, R is calculated from the VI curve, and R is the resistance value of the film; The calculation formula of carrier mobility is: J=9ε0ε r μV 2 / 8L 3 (2) J represents the current density, μ is the carrier mobility, ε0 ​​(8.85×10-12F / m) is the vacuum dielectric constant, and ε r is the dielectric constant of the material itself, V is the open circuit voltage of the film, and L is the thickness of the zinc aluminum oxide film.